Model Pembinaan Pencak Silat di Indonesia: Tinjauan Sistematis Literatur Tahun 2020-2025 - Brahmana Rangga Prastyana; Mohammad Furqon Hidayatullah; Slamet Riyadi; Hanik Liskustyawati (MAN Insan Cendekia Jambi, 2026)
This study aims to analyze the development of Pencak Silat coaching models in Indonesia for the 2020-2025 period through a systematic literature review. The research design employs a systematic review method following the PRISMA guidelines to ensure transparency and replicability of the process. Data sources and search strategy include scientific databases such as Google Scholar, Scopus, and SINTA, using keyword combinations like